Pengaruh Persepsi Mahasiswa Mengenai Lingkungan Kerja Auditor Dan Faktor Sosial Budaya Terhadap Pilihan Karirnya Sebagai Auditor: (Studi Kasus Pada Mahasiswa Akuntansi Universitas Sarjanawiyata Tamansiswa) - Prabowo, Adia Adi; Wardani, Dewi Kusuma; Putri, Fuadhillah Kirana (Politeknik Negeri Ambon, 2023)
This study aims to determine how students' perceptions of the auditor's work environment and socio-cultural factors affect their decision to become auditors in the future. This study covers all undergraduate accounting students at the Faculty of Economics, Sarjanawiyata Tamansiswa University Yogyakarta who are taking auditing courses. A sample of 111 respondents was selected using a purposive sampling technique. The results of data testing show that the decision to become an auditor is influenced by the work environment. On the other hand, socio-cultural factors do not affect the decision to become an auditor. Â